Literature study: The effect of NPK fertilizer application on cucumber plants (Cucumis Sativus L.) - PUTRI MELIYANINGSIH (Nexus: Journal of Cross-Disciplinary Insights, 2025)
This literature review critically evaluates the impact of NPK fertilizer application on cucumber plants (Cucumis sativus L.), with a specific focus on the sustainability and efficiency of fertilizer use. The review examines various studies that investigate the effects of NPK fertilizer on cucumber growth, yield, and fruit quality, as well as the potential environmental risks associated with excessive or inappropriate fertilizer application. The analysis highlights the importance of considering factors such as soil type, cucumber variety, and climatic conditions when designing optimal fertilization strategies. Furthermore, this review emphasizes the need for further research to develop more sustainable fertilization practices that minimize negative environmental impacts while maintaining cucumber crop productivity.